β-glucan-based adjuvants for Hepatitis B vaccination: particulate design for prophylactic and therapeutic needs - Soares, Edna Filipa Pais (2018)
Tese de Doutoramento em Ciências Farmacêuticas, no ramo de Tecnologia Farmacêutica, apresentada à Faculdade de Farmácia da Universidade de Coimbra